Elektrické autobusy - Forman, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Tato bakalářská práce shrnuje poznatky o elektrických autobusech, zejména pak z hlediska rozvržení trakčních komponent ve vozidle. První část se lehce zabývá historií a postupným vývojem elektromobilů a zejména elektrobusů. V druhé části jsou shrnuty nejčastěji využívané zásobníky elektrické energie s uvedením vhodnosti použití pro každý typ. Pozornost je věnována i umístění zásobníků ve vozidle. Následující kapitola se věnuje trakčním elektromotorům, nejčastěji používaným typům a na závěr kapitoly je uvedeno nejběžnější umístění těchto komponent ve vozidle s uvedením výhod a nevýhod pro jednotlivé typy. Ve čtvrté kapitole je výběr elektrických autobusů na současném trhu s důrazem na konstrukční řešení různých výrobců. Předposlední kapitola obsahuje souhrn toho, kam se v současné době trh s elektrobusy posouvá a jaký je aktuální vývoj v této oblasti. Závěrečná kapitola je kapitolou výpočetní a snaží se ukázat zjednodušený postup při výpočtu ideální kapacity baterií na zvolenou trasu elektrobusu.

This bachelor work is dealing with the topic of electric buses, especially from the point of view concerning the design of traction components within the vehicle. The first part of the thesis is concerned with the history and a gradual development of electric cars, especially electro buses. The second part contains the summary of the most commonly used supply chambers of electric energy; the suitability of the usage of types of these supply chambers is also mentioned. The attention is paid to the location of such supply chambers within the vehicle as well. The following chapter is dealing with the traction electric engines – their most commonly used types, and the end of the chapter is concerned with the most usual placement of such components in the vehicle with the list of plus and cons for individual kinds. In the fourth chapter are listed certain types of electric buses in the contemporary market, with the emphasis laid on the construction solution of individual producers. The last but one chapter contains the summary of what direction is the current market of electric buses moving to, and what is the current development of this field. The very last chapter is the practical one, where I am trying to show the simplified method when calculating the optimal capacity of the batteries needed for the chosen route of the electric bus.
Electric buses
Keywords: Elektrobus; baterie; superkapacitor; trakční elektromotor; nízkopodlažní; kapacita; Electric bus; battery; ultracapacitor; traction electric motor; low-floor; capacity